Meningkatkan Kemampuan Passing Bawah Bolavoli Melalui Media Pembelajaran Audio Visual Pada Siswa Kelas IV di UPT SPF SD Inpres Rappokalling I Kota Makassar - Nukhrawi Nawir; Jamaluddin Jamaluddin; Muh. Adnan Hudain; Muhammad Nur Ikram D; Arga Arga (Departement of Mathematics Education, 2023)
This research is a class action research that aims to improve volleyball underhand passing skills through Audio Visual learning media for fourth grade students at UPT SPF SD Inpres Rappokalling I Makassar City. This research was conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects of this study were fourth grade students at, totaling 25 students. There were 14 male students and 11 female students. The technique of collecting data is by testing and observation. Data analysis used quantitative descriptive statistical analysis techniques. The results of the study show that learning through audio-visual media can improve lower passing skills in volleyball games in class IV students. The results of the data obtained from the results of the first cycle of students who completed 48% with a frequency of 12 students and a classical completeness score of 62.3%, then increased in the second cycle of students who completed 84% with a frequency of 21 students and a classical completeness score of 75.3 %. The conclusion of this study is that through audio-visual learning media in learning volleyball underhand passing can improve student learning outcomes in class IV at UPT SPF SD Inpres Rappokalling I Makassar City.